Factores de riesgo en la preeclampsia y su relación con el parto prematuro, en el área de ginecología del Centro de Salud Los rosales, Santo Domingo, periodo 2015 - Mejía López, Silvia Patricia (2016)
The aim of this study was to identify the main risk factors that determine the preeclampsia and eclampsia in women treated at the Health Center in the period Rosales 2015, in order to obtain real, reliable and current data that serve to implement programs Primary health care. The design of this research is descriptive, retrospective and concurrent in 39 patients sampled for ongoing research, medical records of women admitted to the service of gynecology and obstetrics was investigated. In the center we obtained statistical results within three months are January to March we obtained 7 patients with diagnoses; moderate preeclampsia, unspecified, gestational hypertension and hypertension esencial. The poor prenatal, nulliparity, and rural residence were statistically associated with pre-eclampsia, while chronic diseases associated evaluated (chronic hypertension, diabetes mellitus, and renal disease) they were not related to the studied event. The incidence of preeclampsia was 33% and cesarean delivery required 33% of the patients. These findings show the main risk factors for preeclampsia in the studied population, which can serve as clinical markers to detect the disease in early clinical stages and prevent its progression to severe forms.